ISLAM AND FREEDOM: PHILOSOPHICAL AND PRACTICAL ASPECTS (TAMADDUN NURI JURNALI, 2025)
This article examines the idea of ​​freedom in Islamic teachings. The study highlights the personal, religious, and social aspects of freedom and identifies their role in society and state governance. It shows that the idea of ​​freedom in Islam is closely related to moral responsibility and interfaith tolerance. The article offers a scientific approach to harmonizing freedom in Islam with the requirements of the new era.